Algorithmic esthetics meets human intuition: the synergy of innovation and relevance shapes sustained attention - Guan, Wen; Ling, Shuai; Zheng, Li; Zheng, Can (Frontiers in Communication, 2025)
IntroductionArtificial intelligence (AI) technology empowers businesses to bypass designers and create brand logos directly through AI tools. We focus on the effectiveness of AI-generated logos in brand communication when AI acts as an autonomous designer. Relevant research on visual attention has demonstrated the beneficial impact of innovation and relevance on brand communication. However, the combined impact of innovation and relevance on users’ sustained attention in AI-generated logos remains unclear.MethodsTo address this gap, this research demonstrates the synergistic effect of innovation and semantic relevance on users’ sustained attention under different creator type through two studies.ResultsSpecifically, Study 1 explored the synergistic effect of innovation and semantic relevance on cognitive evaluation, emotional evaluation, and sustained attention using 434 questionnaires, and also observed the mediating effect of cognitive evaluation and emotional evaluation. The mediation regression model found that the synergistic effect of innovation and relevance significantly affected users’ cognitive evaluation (F(3,428) = 19.262, MSE = 0.785, p < 0.001) and sustained attention (F(3,428) = 4.197, MSE = 0.737, p < 0.05), with cognitive evaluation playing a mediating effect. Building on these findings, Study 2 verified the moderating effect of creator type by employing 54 valid eye-tracking samples. The results indicate that disclosure of creator type significantly moderates the degree of users’ cognitive evaluation and sustained attention.DiscussionWhen the creator type was disclosed as AI, logos with high innovation and semantic relevance tended to receive sustained attention, and users exhibited more positive cognitive engagement. In contrast, when the creator type was disclosed as human, logos with weak semantic relevance received more sustained attention. These findings provide a basis for integrating AI tools and human creativity in future design.